Whole Mitochondrial Genome Sequence of an Indian Plasmodium falciparum Field Isolate - Tyagi, Suchi (The Korean Society for Parasitology and Tropical Medicine, 2014)
Mitochondrial genome sequence of malaria parasites has served as a potential marker for inferring evolutionary history of the Plasmodium genus. In Plasmodium falciparum, the mitochondrial genome sequences from around the globe have provided important evolutionary understanding, but no Indian sequence has yet been utilized. We have sequenced the whole mitochondrial genome of a single P. falciparum field isolate from India using novel primers and compared with the 3D7 reference sequence and 1 previously reported Indian sequence. While the 2 Indian sequences were highly divergent from each other, the presently sequenced isolate was highly similar to the reference 3D7 strain.